Some Specific Pecularities and Organizational Process of Distance Learning: Beberapa Kekhususan dan Proses Organisasi Pembelajaran Jarak Jauh - Khatamovna, Khalilova Himoyat (Indonesian Journal of Education Methods Development, 2022)
Distance learning - a relationship between a student and a teacher based on Internet technology or other interactive methods and all components of the learning process - goals, content, methods, organizational forms and teaching methods at a certain distance from each other. The all above issues are discussed in this article.